E-beam irradiation effects on IR absorption bands in single-walled carbon nanotubes. (January 2017) - Ichida, Masao; Nagao, Katsunori; Ikemoto, Yuka; Okazaki, Toshiya; Miyata, Yasumitsu; Kawakami, Akira; Kataura, Hiromichi; Umezu, Ikurou; Ando, Hiroaki
Abstract: We have measured the absorption and Raman spectral change induced by the irradiation of e-beam. By the irradiation of e-beam on SWNTs thin films, the intensity of defect related Raman band increase, and the peak energy of IR absorption bands shift to the higher energy side. These results indicate that the origin of infrared band is due to the plasmon resonance of finite-length SWNT. We have estimated the effective tube length and defect density from IR absorption peak energy. Highlights: High purity semiconducting and metallic single-walled carbon nanotubes (SWNTs) films. Broad Infrared (IR) absorption bands are observed below 0.5 eV for both samples. By the irradiation of e-beam on SWNTs thin films, the intensity of defect related Raman band increase, and the peak energy of IR absorption bands shift to the higher energy side. These results indicate that the origin of infrared band is due to the optical resonance of finite-length SWNT which is determined by the defect density.